Assessment of household-level adaptation strategies to water stress in southwestern coastal Bangladesh: a counter-factual analysis. Issue 9 (12th August 2022) - Ahsan, Md. Nasif; Khatun, Fatema; Islam, Md. Sariful; Hossain, Md. Sarwar; Mou, Benzir Huq; Kumar, Pankaj
Abstract: Despite the growing emphasis and global initiatives to ensure safe drinking water and sanitation for all (Sustainable Development Goal 6), households in coastal areas are at risk of growing water stress across the globe. However, little is known about households' adaptation strategies to water stress in coastal areas. This study explores the determinants and impacts of adaptation strategies to household-level water stress (both drinking and non-drinking), considering the behaviors of adopters and non-adopters in the southwestern coastal area of Bangladesh. We applied an endogenous switching regression model by analyzing questionnaire survey datasets ( n =502) to estimate the effect of adopting adaptation strategies on household-level water stress in four saline-prone coastal sub-districts of Bangladesh. Results reveal six commonly-practiced adaptation strategies: reducing vegetable production, reducing livestock production, paying more to access water, increasing time for water collection, preserving water, and using reservoirs to collect water. Determinants such as migration, support from government and non-government agencies, age, gender, literacy, occupation, income, access to tube wells, and distance from drinking water sources play a significant role in adopting adaptation strategies. Results from the endogenous switching regression model denote that adopting all six adaptation strategies appears to significantly reduce household-level water stress. Through counter-factual analysis, results demonstrate that, on average, households that did not adopt adaptation strategies would have encountered less water stress if they had. Therefore, determinants that stimulate adaptation strategies will indirectly reduce household water stress. HIGHLIGHTS: Six distinct adaptation strategies are identified to withstand water stress. Different socioeconomic determinants and migration significantly affected the adoption of the adaptation strategies. Endogenous Switching Regression Model is applied. Counter-factual analysis presents the difference in treatment effects between adopters and non-adopters of six adaptation strategies. Graphical Abstract